DOLORisk: study protocol for a multi-centre observational study to understand the risk factors and determinants of neuropathic pain - Pascal, M; Themistocleous, AC; Baron, R; Binder, A; Bouhassira, D; Crombez, G; Finnerup, NB; Gierthmühlen, J; Granovksy, Y; Groop, L; Hebert, HL; Jensen, TS; et al. (Wellcome Trust, 2018)
Background Neuropathic pain is an increasingly prevalent condition and has a major impact on health and quality of life. However, the risk factors for the development and maintenance of neuropathic pain are poorly understood. Clinical, genetic and psychosocial factors all contribute to chronic pain, but their interactions have not been studied in large cohorts. The DOLORisk study aims to study these factors. Protocol Multicentre cross-sectional and longitudinal cohorts covering the main causes leading to neuropathic pain (e.g. diabetes, surgery, chemotherapy, traumatic injury), as well as rare conditions, follow a common protocol for phenotyping of the participants. This core protocol correlates answers given by the participants on a set of questionnaires with the results of their genetic analyses. A smaller number of participants undergo deeper phenotyping procedures, including neurological examination, nerve conduction studies, threshold tracking, quantitative sensory testing, conditioned pain modulation and electroencephalography.